New isolate of Bacillus thuringiensis effective against the fall armyworm - Werneck, Joseilde Oliveira Silva; Neto, José Ricardo de Moraes Veiga Abreu; Tostes, Adriana Nascimento; Faria, Líliam Oliveira; Dias, José Manuel Cabral de Sousa (Pesquisa Agropecuaria Brasileira, 2000)
Aiming to identify active ingredients that can be used to control the fall armyworm, Spodoptera frugiperda (Smith, 1797), 205 isolates of Bacillus from samples of different Brazilian regions were assayed against this insect. Only one isolate of B. thuringiensis subsp. kurstaki, designed S93, caused 100% mortality. The LC50 of spores-crystals mixture of S93 against 3th instar larvae of S. frugiperda was 37.0 ng/mL, while the LC50 for the strain HD-1 of B. thuringiensis subsp. kurstaki, isolated from the product Dipel, was 177.73 mg/mL, showing that this new isolate is much more active against the fall armyworm than the HD-1-Dipel.